Linkages between the Genesis and Resource Potential of Ferromanganese Deposits in the Atlantic, Pacific, and Arctic Oceans - Amaya Menendez; Rachael James; Natalia Shulga; Doug Connelly; Steve Roberts (Minerals, 2018)
In addition to iron and manganese, deep sea ferromanganese deposits, including nodules and crusts, contain significant amounts of economically interesting metals, such as cobalt (Co), nickel (Ni), copper (Cu), and rare Earth elements and yttrium (REY). Some of these metals are essential in the development of emerging and new-generation green technologies. However, the resource potential of these deposits is variable, and likely related to environmental conditions that prevail as they form. To better assess the environmental controls on the resource potential of ferromanganese deposits, we have undertaken a detailed study of the chemical composition of ferromanganese nodules and one crust sample from different oceanic regions. Textural and chemical characteristics of nodules from the North Atlantic and a crust from the South Pacific suggest that they acquire metals from a hydrogenous source. These deposits are potentially an economically important source of Co and the REY. On the other hand, nodules from the Pacific Ocean represent a marginal resource of these metals, due to their relatively fast growth rate caused by diagenetic precipitation. By contrast, they have relatively high concentrations of Ni and Cu. A nodule from the Arctic Ocean is characterised by the presence of significant quantities of detrital silicate material, which significantly reduces their metal resource.